Acute Right Middle Cerebral Artery Occlusion Resulting in Acute Systolic Heart Failure, Cerebral T-Waves, and QTc Prolongation: A Case Report. Issue 4 (July 2018) - Blech, Benzion; O'Carroll, Cumara
Abstract : Introduction: Acute cerebral injuries, such as cerebral ischemic or hemorrhagic events, have been repeatedly correlated with sudden electrocardiogram (ECG) changes, such as cardiac arrhythmias, QT prolongation, and T-wave inversion (the "cerebral T-wave"). Injuries to the insular cortex have been reported in the literature to result in such changes, possibly due to increased sympathetic tone to the cardiac system. Case Report: A 65-year-old gentleman presented with an acute right middle cerebral artery territory infarction, and was found to have ECG abnormalities and left ventricular dysfunction, which improved after the acute phase of the stroke. Conclusions: Acute ischemic infarcts, particularly to the right insular cortex, can result in ECG abnormalities, such as QT prolongation and T-wave inversion, as well as acute systolic heart failure; all of which may be reversible after the acute phase of the stroke.